Application of chitosan encapsulated clove essential oil microcapsules on cotton fabrics for antibacterial finish (Indian Journal of Fibre & Textile Research (IJFTR), 2024)
The current investigation delves into the viability of spray-dried environment, friendly clove essential oil (CEO) microcapsules in chitosan biopolymer to enhance the antibacterial activity of cotton fabrics. The process parameters, such as core-to-wall ratio, oil concentration, sheath, surfactants, cross-linkers, and spray drying machine parameters like inlet temperature, feed rate, and atomization pressure, are optimized using Box Behnken design and central composite design. The investigation ascertains the average particle size for the CEO microcapsules to be below 2 μm, with microencapsulation efficiency ranging from 40% to 72%. The microcapsules are characterized using Fourier transform infrared spectroscopy, scanning electron microscopy, transmission electron microscopy and thermogravimetric analysis. The CEO microcapsules are also prepared using sodium tripolyphosphate as cross-linker with the chitosan sheath. The study involves applying CEO microcapsules prepared with and without cross-linker on 100% cotton fabrics by a padding technique with three different cross-linkers, viz malic acid, maleic acid and Eudragit S 100. The evaluation of wash durability, antibacterial efficacy, and physical characteristics, such as tensile strength and air permeability, has been carried out using appropriate methods. A comparative assessment of using different cross-linkers to apply microcapsules on cotton fabrics is undertaken. The Eudragit S 100 is found to be the most appropriate cross-linker to achieve antibacterial properties and better physical attributes of thetreated cotton fabrics.